Taxonomy-alignment and transition risk: A country-level approach - Lucia Alessi; Stefano Battiston (European Commission, 2023)
When firm-level information is not available, the greenness of financial portfolios, in terms of alignment to the EU Taxonomy, and their exposure to climate-related transition risk need to be estimated with a top-down approach. We improve the accuracy of available estimates by providing country-specific coefficients for both dimensions, based on homogeneous definitions of greenness and transition risk across countries. An application on confidential data from the European Central Bank shows that the exposure to transition risk of less regulated financial institutions has more than tripled from 2014 to 2023. Moreover, we show that the levels of Taxonomy alignment and transition risk exposure are largely heterogeneous across countries and sectors.
Keywords: G2; G3; Q54; 330; greenness; climate-related transition risk; climate-related financial disclosures; EU Taxonomy; green financial flows